2008
DOI: 10.1021/ma7022099
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling of Novel Fullerene-Grafted Donor–Acceptor Rod−Coil Block Copolymers

Abstract: Fullerene-grafted rod−coil block copolymers, designed for being used as active polymer layers in donor–acceptor bulk heterojunction photovoltaic devices, have been synthesized. The copolymer synthesis was monitored by 1H nuclear magnetic resonance, size exclusion chromatography and infrared absorption spectroscopy, while the material properties were explored by X-ray diffraction, atomic force microscopy, UV–vis absorption, and photoluminescence spectroscopy. Structural properties of bulk materials and thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
108
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 43 publications
1
108
3
Order By: Relevance
“…82 To rectify one of the problems with PCBM (namely its tendency to undergo excessive crystallization), research has effectively demonstrated the use of cross-linking groups. 83,84 Of similar interest are polymers carrying pendent fullerenes, 85 although they tend to suffer from aggregative effects of C 60 rather than self-assembly, 86 or linear main-chain polymers based on C 60 as a monomer, which seem to have displayed morphologies more appropriate to charge collection and transfer. 87 Further work on other acceptors such as perylene, notably perylene tetracarboxydiimide (PDI), 88,89 the poly(benzimidazobenzophenanthroline) ladder (BBL), 90 and units based on 9,9'-bifluorenylidene, 91 conversely, have shown that fullerene may not be necessary.…”
Section: Figurementioning
confidence: 99%
“…82 To rectify one of the problems with PCBM (namely its tendency to undergo excessive crystallization), research has effectively demonstrated the use of cross-linking groups. 83,84 Of similar interest are polymers carrying pendent fullerenes, 85 although they tend to suffer from aggregative effects of C 60 rather than self-assembly, 86 or linear main-chain polymers based on C 60 as a monomer, which seem to have displayed morphologies more appropriate to charge collection and transfer. 87 Further work on other acceptors such as perylene, notably perylene tetracarboxydiimide (PDI), 88,89 the poly(benzimidazobenzophenanthroline) ladder (BBL), 90 and units based on 9,9'-bifluorenylidene, 91 conversely, have shown that fullerene may not be necessary.…”
Section: Figurementioning
confidence: 99%
“…Phase separation of a copolymer consisting of a donor block and an acceptor block may be a straightforward way to generate an ideal OPV morphology. Reported energy conversion efficiencies using this approach have not been high: Hazdiioannou's group has several reports on synthesizing BCPs containing PPV and C 60 , with the latter grafted onto polystyrene [76]. A small photovoltaic effect under monochromatic illumination was demonstrated [77].…”
Section: Current Progress Using Donor-acceptor Bcpsmentioning
confidence: 99%
“…[14][15][16][17][18][19] Block copolymers composed of an electron-donating and an electronaccepting block are therefore particularly interesting for PV applications and are presently studied worldwide by several research groups. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Particularly, rod-coil block copolymers using poly[(2,5-di(2-ethyl)hexyloxy)-1,4-phenylenevinylene] (DEH-PPV) as electron donor and various coil blocks (such as polystyrene or polybutylacrylate) with covalently linked fullerene moieties as electron acceptor have been investigated intensively. [23][24][25][26][27][28] Although these studies have given considerable insight into the physics of copolymer self-assembly, their efficient utilization as the active layer in PV devices has not yet been fully demonstrated.…”
mentioning
confidence: 99%
“…Also, in the case of block copolymer/fullerene blends, the copolymer microphase separation has been found to be less affected by the C 60 crystallization than for fullerene-grafted block copolymers. [34,39] In particular, the pristine DEH-PPV-b-P4VP nanostructure was shown to be preserved when blended with 10% C 60 and to be thermally stable up to at least 16 h at 180 8C. [39] Finally the PCBM fullerene derivative was chosen for its high solubility in common solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation